2014
DOI: 10.1177/1479972314556086
|View full text |Cite
|
Sign up to set email alerts
|

A test of vitamin D benefits on respiratory health mediated through inflammatory markers

Abstract: Previous studies have shown that vitamin D has beneficial effects on respiratory health. The role of inflammation as a possible mediator between vitamin D and respiratory health is not well understood. We used National Health and Nutrition Examination Survey 2001Survey -2006 to examine the mediating effects of biomarkers of inflammation on associations between vitamin D and respiratory health. Vitamin D was measured by serum 25 hydroxy vitamin D test. Respiratory health was measured by self-reported respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Although the current study cannot provide information on respiratory function, disease severity or exacerbation frequency, we do report data on CRP concentrations similar to other stable COPD cohorts55 and which may be a possible mediating factor between vitamin D and respiratory function 52. In the current study, CRP did not differ significantly between the seasons and was not correlated with serum 25(OH)D concentration at either time point, a finding that confirms the findings of others 52.…”
Section: Discussionsupporting
confidence: 85%
“…Although the current study cannot provide information on respiratory function, disease severity or exacerbation frequency, we do report data on CRP concentrations similar to other stable COPD cohorts55 and which may be a possible mediating factor between vitamin D and respiratory function 52. In the current study, CRP did not differ significantly between the seasons and was not correlated with serum 25(OH)D concentration at either time point, a finding that confirms the findings of others 52.…”
Section: Discussionsupporting
confidence: 85%
“…provided a potential explanation related to oxidative stress and inflammation, which was associated with the development of type 2 diabetes . Smokers have increased oxidative stress and inflammation and since it is thought that vitamin D may have antioxidant and anti‐inflammatory effects, vitamin D status may have a differential effect in smokers and non‐smokers. In a recent study of elderly subjects, the association between vitamin D deficiency and c‐reactive protein (a biomarker of systemic inflammation) was stronger in smokers compared to non‐smokers .…”
Section: Discussionmentioning
confidence: 99%
“…48 In noncritically ill subjects, 25(OH)D deficiency has been associated with chronic obstructive pulmonary disease and respiratory symptoms. 50 In retrospective and prospective observational studies of ICU patients, 25(OH)D levels were inversely associated with mechanical ventilation days in medical ICU patients (10.04 6 1.97 days in vitamin D-deficient group vs. 3.15 6 0.15 days in vitamin D sufficient group, P 5 0.003) 45 and critically ill surgical patients (incident risk ratio per 10 ng/mL 5 0.66, 95% CI 5 0.39-0.66, P , 0.05) 48 ; however, in another study, there was no observed association between vitamin D deficiency and mechanical ventilation. 42 …”
Section: Respiratorymentioning
confidence: 97%